The Impact of Key Determinants of BIM Technology Adoption on Organizational Performance within the UAE Construction Industry - Abdulrahim, Amina (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)